Cancer‐Cell‐Specific Drug Delivery by a Tumor‐Homing CPP‐Gossypol Conjugate Employing a Tracelessly Cleavable Linker. Issue 14 (30th January 2020) - Maity, Suman Kumar; Stahl, Paul; Hensel, Astrid; Knauer, Shirley; Hirschhäuser, Christoph; Schmuck, Carsten
Abstract: Tumor‐targeted drug delivery is highly important for improving chemotherapy, as it reduces the dose of cytotoxic agents and minimizes the death of healthy tissues. Towards this goal, a conjugate was synthesized of gossypol and a MCF‐7 cancer cell specific CPP (cell penetrating peptide), thus providing a selective drug delivery system. Utilizing the aldehyde moiety of gossypol, the tumor homing CPP RLYMRYYSPTTRRYG was attached through a semi‐labile imine linker, which was cleaved in a traceless fashion under aqueous conditions and had a half‐life of approximately 10 hours. The conjugate killed MCF‐7 cells to a significantly greater extent than HeLa cells or healthy fibroblasts. Abstract : Selective drug delivery : A Cancer‐cell specific drug delivery system was developed by conjugating a tumor homing peptide and gossypol through a cleavable linker. The Schiff's base linked conjugate killed the targeted MCF‐7 cells selectively compared to HeLa cells used as a control (see figure).